Toxicity of Granule from Sugar Apple (Annona squamosa. L) Fruit Extract on The Mortality Aedes aegypti Larvae - Dini Aisyafahmi; Dwi Wahyuni (BIOEDUKASI, 2017)
Aedes aegypti L. is mosquito belong to the order diptera that widely distributed in the tropics. Female Aedes aegypti L. is the primary vector for the spread of dengue fever. Dengue fever has increased from year to year. Efforts to eradicate the disease done by government mainly using chemical insecticides which their residues can endanger non-target organisms. Eco-friendly Aedes aegypti L. larvae's control is needed to suppress the populations. One that can be achieve using natural larvacide from sugar apple (Annona squamosa L.). The aim of this research was to find out the LC 50 and toxicty effect of granule from sugar apple extract (Annona squamosa L.) on Aedes aegypti L. larvae’s mortality. The concentration used in this research were 1, 5, 25, 50, 75, 100, 125, 150 ppm, control 0 In the form of tween 80, positive control abate and negative control aquades. The result shows that LC 50 granule extract of apple sugar (Annona squamosa L.) was 8.25 ppm. Keywords: Aedes aegypti L., Annona squamosa L., granule, toxicity, LC 50